Pengaruh Literasi Keuangan, Pengendalian Diri, Kelompok Teman Sebaya dan Kondisi Sosial Ekonomi Orang Tua Terhadap Perilaku Konsumtif Peserta Didik - Murdiyanti, Uki; Basukiyatno, Basukiyatno; Habibi, Beni (Universitas Pancasakti Tegal, 2021)
Consumptive behaviour in adolescents arises because they want to show that they can also follow the fashions nowadays, join in with friends, want to look different from others and tend to be never satisfied with what they already have. Consumptive behaviour begins to emerge when there is a change in the pattern of consumption behaviour, namely irrational consumption behaviour or only due to emotional factors. This research aims to know 1)the effect parsial of financial literacy on the comsumptive behavior, 2) The effect self-contrl on the comsumptive behavior, 3) The effect peer groups on the comsumptive behaviorand 4)the effect socio-economic conditions of parents on the consumptive behaviour of Grade XI students also 5)to know the effect simultan of financial literacy, self-control, peer groups and the socio-economic conditions of parents on the consumptive behaviour of Grade XI students of SMK NU 1 Islamiyah Kramat. The population of this research were students of SMK NU 1 Islamiyah Kramat, Class XI Accaountancy One for 93 students consisting of 3 classes, XI Accountancy class as many as 93 students, XI Accountancy One as many 31 student, Accountancy Two class as many as 30 students and XI Accountancy Three class as many as 32 students. The sampling technique uses proportional random sampling technique. Data collection techniques using a paper or questionnaire that has been tested for validity and reliability. Data analysis techniques using descriptive statistics and multiple linear regression analysis. The effect of financial literacy on consumptive behaviour is 48,5%, self-control has an effect on consumptive behaviour by 27.8%, peer group has an effect of 15.2% and the socio-economic conditions of parents have an effect of 21.4%. The regression equation Y = 17,878-0,379 X1-0,195 X2 + 0,168 X3 + 0,382X4. There is an effect of financial literacy, self-control, peer groups and the socio-economic conditions of parents on consumptive behaviour collectively are 71,8% and the other variabel is 29,3% Based on the results of this research, students are expected to be able to make a priority scale before making a purchase transaction. So that students have a good literacy financial do not have consumptive behaviour.